Inner-Biblical Allusion and the Direction of Dependence: Toward a Comprehensive List of Criteria - Smith, Cooper (Journal of Hebrew Scriptures, 2022)
A prevailing need in biblical studies is a comprehensive set of valid arguments for determining the direction of dependence once a literary relationship between two texts in the Hebrew Bible is reasonably established. This study takes a step toward addressing this lacuna by inductively cataloguing, illustrating, and evaluating eight criteria used to substantiate a proposed direction of borrowing in cases of inner-biblical allusion in Isaianic scholarship. These criteria provide a working list of plausible arguments that can be used when claiming the direction of influence in other cases of inner-biblical allusion throughout the Hebrew Bible. Such a list encourages both methodological clarity due to the increased precision of defined categories and scholarly creativity by suggesting multiple viable means to argue for the direction of dependence.